Inbreeding calculation in the recurrent family selection in maize - Márquez-Sánchez, Fidel (Revista Mexicana de Ciencias Agrícolas, 2018)
Recurrent selection ensures an improved long-term yielding; also the breeder may obtain partial results in any selection cycle. Recurrent selection has been practiced by a number of researchers in maize, obtaining responses per cycle that have guaranteed to continue this method through twenty or more cycles of selection. However, the author is unaware that except in one research, inbreeding generated through the selection has been calculated. Therefore, the present study aims to review that research and propose a better approach.
Keywords: Zea mays L.; recurrent selection; family types in maize; theory of inbreeding